2019
DOI: 10.1186/s13012-019-0887-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance comparators in audit and feedback: a review of theory and evidence

Abstract: Background Audit and feedback (A&F) is a common quality improvement strategy with highly variable effects on patient care. It is unclear how A&F effectiveness can be maximised. Since the core mechanism of action of A&F depends on drawing attention to a discrepancy between actual and desired performance, we aimed to understand current and best practices in the choice of performance comparator. Methods We described current choices for performance comparators by conducting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 102 publications
(242 reference statements)
1
79
0
1
Order By: Relevance
“…We believe that the high compliance and the key factors of the persistence of multimodal intervention to control MDROs in LMICs were associated closely to the following issues: (1) practicable A&F interventions on improving quality needs an organizational structure and strong leadership in the institute [19,22]; (2) it is more practicable to transform main components into standardized implementation indicators that can be observed objectively in auditing 35 ; (3) quantitative analysis can help to count or measure what is happening now and guide clinical practices [26]; (4) specifying the working scope of doctors and nurses to construct separate implementation indicators, feedback and education can greatly enhance the intervention implementation; (5) benchmark comparison clearly from feedback report could inspire clinical staff to improve the implementation on those indicators below benchmark e ciently according to the control theory [22,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the high compliance and the key factors of the persistence of multimodal intervention to control MDROs in LMICs were associated closely to the following issues: (1) practicable A&F interventions on improving quality needs an organizational structure and strong leadership in the institute [19,22]; (2) it is more practicable to transform main components into standardized implementation indicators that can be observed objectively in auditing 35 ; (3) quantitative analysis can help to count or measure what is happening now and guide clinical practices [26]; (4) specifying the working scope of doctors and nurses to construct separate implementation indicators, feedback and education can greatly enhance the intervention implementation; (5) benchmark comparison clearly from feedback report could inspire clinical staff to improve the implementation on those indicators below benchmark e ciently according to the control theory [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, benchmarking techniques could help participants in A&F avoid setting unnecessarily low or unrealistically high target levels of performance [22]. Our quasi-experiment study aimed to assess the impact of multimodal intervention which treated A&F and benchmark as key components to reduce the occurrence of MDROs and the implementation effect in three Chinese public hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…We found that healthcare providers received irregular supervision visits with limited focus on performance improvement at the clinical level. Findings and recommendations regarding benchmarking [32], the use of SMART (Speci c, Measurable, Achievable, Relevant and Timely) criteria, concepts from social nudging and Enhanced active choice [33], and the Model of Actionable Feedback [13], informed the design of the QID. eRegistry users', nursing and medical directors', and PNIPH and MoH staff's reviews informed the revisions.…”
Section: The Quality Improvement Dashboard Interventionmentioning
confidence: 99%
“…The optimism that feedback of audit data would promote corrective action has been the subject of academic examination and is far from validated [23,24]. In practice, the early RA default assumption, that closure of audit cycles would be attempted at unit level, left some discomfort in the UKRR [25].…”
Section: Main Textmentioning
confidence: 99%